2013
DOI: 10.1021/cb400125w
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Synthesis and Screening of a Sialoside Library Yields a High Affinity Ligand for Siglec-7

Abstract: The Siglec family of sialic acid-binding proteins are differentially expressed on white blood cells of the immune system and represent an attractive class of targets for cell-directed therapy. Nanoparticles decorated with high-affinity Siglec ligands show promise for delivering cargo to Siglec-bearing cells, but this approach has been limited by a lack of ligands with suitable affinity and selectivity. Building on previous work employing solution-phase sialoside library synthesis and subsequent microarray scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 26 publications
0
73
0
1
Order By: Relevance
“…In an on-chip glycan array screen, Rillahan et al have found that clicking distinct azide groups to sialic acids can strongly enhance their binding affinity to Siglec-7. 49 From this on-chip screen, we have selected three azides derivatives (azide1−3) that either strongly enhance Siglec-7 binding (azide 1), led to an intermediate increase in Siglec-7 binding (azide 2), or did not enhance Siglec-7 binding (azide 3) (Figure 5a). 49 THP-1 or Jurkat cells were treated with Ac 4 ManNPoc or Ac 5 NeuNPoc, and the three different azides were clicked to the Poc-modified glycans using CuAAC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In an on-chip glycan array screen, Rillahan et al have found that clicking distinct azide groups to sialic acids can strongly enhance their binding affinity to Siglec-7. 49 From this on-chip screen, we have selected three azides derivatives (azide1−3) that either strongly enhance Siglec-7 binding (azide 1), led to an intermediate increase in Siglec-7 binding (azide 2), or did not enhance Siglec-7 binding (azide 3) (Figure 5a). 49 THP-1 or Jurkat cells were treated with Ac 4 ManNPoc or Ac 5 NeuNPoc, and the three different azides were clicked to the Poc-modified glycans using CuAAC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…cellular autofluorescence). For hCD33-ligand specificity analysis with overexpressing recombinant cell lines, 28, 31, 32 1% ligand-displaying liposomes were used. This panel of cell lines consists of CHO cells expressing mSn, hSig3, hSig5, hSig8, hSig9, and hSig10, Jurkat cells expressing hSig7, and Ramos cells expressing hCD22 (other B-cell lines were found to express additional siglecs, data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Modified sialic acids with alkyne groups in positions five and nine were immobilized in NHS modified glass slides, and subjected to CuAAC reactions with 47 different azido compounds. The modified sialic acids generated on chip were screened towards Siglec-7 and Siglec-10, permitting characterization of a high affinity ligand for Siglec-7 [49].…”
Section: Glycan Binding Proteinsmentioning
confidence: 99%
“…First examples in this direction are the enzymatic on-chip diversification of glycan scaffolds in nano-droplets [17], or the on-chip synthesis of potential Siglec antagonists employing click reactions for the introduction of a second library of structural substituents [49].…”
Section: Detection Of Serum Anti-carbohydrate Antibodies Anticancer Vmentioning
confidence: 99%